The effect of transformational leadership styles towards managing knowledge assets - Hazlina Hassan,; Noradiva Hamzah,; Norman Mohd Saleh,; Amrizah Kamaluddin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Effectiveness in managing knowledge asset is essential to improve the quality services and to enhance performance. The purpose of this study is to explore on how hospitals extracting the value of their knowledge assets in order to sustain and be competitive by considering leadership styles factors. The data collection was carried out by survey. Questionnaires were distributed to all top management team of private hospitals in Malaysia. From the survey, the results indicate that transformational leadership styles are significantly related to the knowledge assets element. This suggests that some hospitals might use the characteristics of transformational leadership styles such as idealized influence, inspirational motivation, intellectual stimulation and individualized consideration to enhance knowledge assets management. The findings might also assist the regulators and managers of the hospitals to formulate strategies in enhancing governance of knowledge assets.